FOUR ESSAYS ON THE LINKS BETWEEN POVERTY, INEQUALITY AND HEALTH WITH EMPIRICAL APPLICATION TO DEVELOPING COUNTRIES: AFRICA COMPARED TO THE REST OF THE WORLD - (:unkn) unknown (My University, 2009)
In this dissertation, we are mainly interested in the interactions between poverty and one of its greatest dimensions1, namely health. More specifically, we will focus on their inequalities: does poverty inequality have more effect on poverty than health level? Does health inequality matter to poverty? Poverty and health are two related concepts that both express human deprivation. Health is said to be one of the most important dimensions of poverty and vice-versa. That is, poverty implies poor health because of a low investment in health, a bad environment and sanitation and other living conditions due to poverty, a poor nutrition (thus a greater risk of illness), a limited access to, and use of, health care, a lower health education and investment in health, etc2. Conversely, poor health leads inevitably to poverty due to high opportunity costs occasioned by ill-health such as unemployment or limited employability (thus a loss of income and revenues), a lower productivity (due to loss of strength, skills and ability), a loss of motivation and energy (which lengthen the duration of job search), high health care expenditures (or catastrophic expenditures), etc3. But what are the degree of correlation and the direction of the causality between these two phenomena? Which causes which? This is a classic problem of simultaneity that has become a great challenge for economists. Worst, each of these phenomena (health and poverty) has many dimensions4. How to reconcile two multidimensional and simultaneous events? 1 Aside the income-related material deprivation. 2 Tenants of the ?Absolute Income? hypothesis for instance show that absolute income level of individual has positive impact on their health status (Preston, 1975; Deaton, 2003). Conversely, lack of income (and the poverty state it implies) leads unambiguously to poor health. For other authors, it is not the absolute level per se, but the relative level (i.e. comparably to others in the society) that
Keywords: African Research